Questions & Answers

Question

Answers

Answer

Verified

146.4k+ views

Hint: Assume the numbers as (a – d), a, (a + d) and apply the conditions to solve to get the values of ‘a’ and ‘d’ and after that put that values in assumed numbers to get the answer.

Complete step-by-step answer:

As we have given that the three numbers are in A.P. and therefore we will assume (a-d), a, (a+d) as the three numbers in A.P. with ‘a’ as the first term and‘d’ is the common difference.

As the sum of three numbers is 12, therefore we can write,

(a - d) + a + (a + d) = 12

$\Rightarrow $a - d + a + a + d = 12

$\Rightarrow $a + a + a = 12

$\Rightarrow $ 3a = 12

$\Rightarrow a=\dfrac{12}{3}$

$\Rightarrow $ a = 4 …………………………………. (2)

Now, as per the second condition given in the problem we can write,

$\therefore {{\left( a-d \right)}^{3}}+{{a}^{3}}+{{\left( a+d \right)}^{3}}=408$

If we put the value equation (2) in the middle term of the above equation we will get,

$\Rightarrow {{\left( a-d \right)}^{3}}+{{4}^{3}}+{{\left( a+d \right)}^{3}}=408$

$\Rightarrow {{\left( a-d \right)}^{3}}+64+{{\left( a+d \right)}^{3}}=408$

$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=408-64$

$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ ………………………………… (3)

Now to proceed further in the solution we should know the formula given below,

Formula:

\[\left( {{x}^{3}}+{{y}^{3}} \right)=\left( x+y \right)\times \left( {{x}^{2}}+{{y}^{2}}-xy \right)\]

By using above formula we can write equation (3) as follows,

\[\therefore \left[ \left( a-d \right)+\left( a+d \right) \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]

\[\therefore \left[ a-d+a+d \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]

\[\therefore \left[ a+a \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}+ad-ad-{{d}^{2}} \right) \right]=344\]

\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}-{{d}^{2}} \right) \right]=344\]

\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]

Now to proceed further we should know the formulae given below,

Formulae:

\[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}+2xy+{{y}^{2}} \right)\] And \[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}-2xy+{{y}^{2}} \right)\]

By using the above formulae we can write the above equation as,

\[\therefore 2a\times \left[ \left( {{a}^{2}}-2ad+{{d}^{2}} \right)+\left( {{a}^{2}}+2ad+{{d}^{2}} \right)-{{a}^{2}}+{{d}^{2}} \right]=344\]

By opening the brackets we will get,

\[\Rightarrow 2a\times \left[ {{a}^{2}}-2ad+{{d}^{2}}+{{a}^{2}}+2ad+{{d}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]

\[\Rightarrow 2a\times \left[ {{d}^{2}}+{{a}^{2}}+{{d}^{2}}+{{d}^{2}} \right]=344\]

\[\Rightarrow 2a\times \left[ 3{{d}^{2}}+{{a}^{2}} \right]=344\]

By substituting the value of equation (2) in the above equation we will get,

\[\Rightarrow 2\times 4\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]

\[\Rightarrow 8\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]

\[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]

\[\Rightarrow 3{{d}^{2}}+16=43\]

\[\Rightarrow 3{{d}^{2}}=43-16\]

\[\Rightarrow 3{{d}^{2}}=27\]

\[\Rightarrow {{d}^{2}}=\dfrac{27}{3}\]

\[\Rightarrow {{d}^{2}}=9\]

By taking square roots on both sides of the equation we will get,

\[\therefore d=\pm 3\]

Therefore d = 3 OR d = -3 ……………………………………. (4)

Now we will rewrite the three numbers below,

(a – d), a, (a + d)

If we put the values of equation (2) and equation (4) in above equation as shown below,

a = 4 and d = 3

Therefore numbers will become,

(4 – 3), 4, (4+3)

Therefore the numbers are,

1, 4, 7.

Now,

a = 4 and d = - 3

Therefore numbers will become,

[4 – (-3)], 4, [4+(-3)]

(4 + 3), 4, (4 – 3)

Therefore the numbers are,

7, 4, 1.

Therefore the three numbers are 1, 4, 7 or 7, 4, 1.

Note: Assume the standard numbers given by (a – d), a, (a + d) to make the calculations easier. Also in the step ${{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ you can also use the formulae of \[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]

Complete step-by-step answer:

As we have given that the three numbers are in A.P. and therefore we will assume (a-d), a, (a+d) as the three numbers in A.P. with ‘a’ as the first term and‘d’ is the common difference.

As the sum of three numbers is 12, therefore we can write,

(a - d) + a + (a + d) = 12

$\Rightarrow $a - d + a + a + d = 12

$\Rightarrow $a + a + a = 12

$\Rightarrow $ 3a = 12

$\Rightarrow a=\dfrac{12}{3}$

$\Rightarrow $ a = 4 …………………………………. (2)

Now, as per the second condition given in the problem we can write,

$\therefore {{\left( a-d \right)}^{3}}+{{a}^{3}}+{{\left( a+d \right)}^{3}}=408$

If we put the value equation (2) in the middle term of the above equation we will get,

$\Rightarrow {{\left( a-d \right)}^{3}}+{{4}^{3}}+{{\left( a+d \right)}^{3}}=408$

$\Rightarrow {{\left( a-d \right)}^{3}}+64+{{\left( a+d \right)}^{3}}=408$

$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=408-64$

$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ ………………………………… (3)

Now to proceed further in the solution we should know the formula given below,

Formula:

\[\left( {{x}^{3}}+{{y}^{3}} \right)=\left( x+y \right)\times \left( {{x}^{2}}+{{y}^{2}}-xy \right)\]

By using above formula we can write equation (3) as follows,

\[\therefore \left[ \left( a-d \right)+\left( a+d \right) \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]

\[\therefore \left[ a-d+a+d \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]

\[\therefore \left[ a+a \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}+ad-ad-{{d}^{2}} \right) \right]=344\]

\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}-{{d}^{2}} \right) \right]=344\]

\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]

Now to proceed further we should know the formulae given below,

Formulae:

\[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}+2xy+{{y}^{2}} \right)\] And \[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}-2xy+{{y}^{2}} \right)\]

By using the above formulae we can write the above equation as,

\[\therefore 2a\times \left[ \left( {{a}^{2}}-2ad+{{d}^{2}} \right)+\left( {{a}^{2}}+2ad+{{d}^{2}} \right)-{{a}^{2}}+{{d}^{2}} \right]=344\]

By opening the brackets we will get,

\[\Rightarrow 2a\times \left[ {{a}^{2}}-2ad+{{d}^{2}}+{{a}^{2}}+2ad+{{d}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]

\[\Rightarrow 2a\times \left[ {{d}^{2}}+{{a}^{2}}+{{d}^{2}}+{{d}^{2}} \right]=344\]

\[\Rightarrow 2a\times \left[ 3{{d}^{2}}+{{a}^{2}} \right]=344\]

By substituting the value of equation (2) in the above equation we will get,

\[\Rightarrow 2\times 4\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]

\[\Rightarrow 8\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]

\[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]

\[\Rightarrow 3{{d}^{2}}+16=43\]

\[\Rightarrow 3{{d}^{2}}=43-16\]

\[\Rightarrow 3{{d}^{2}}=27\]

\[\Rightarrow {{d}^{2}}=\dfrac{27}{3}\]

\[\Rightarrow {{d}^{2}}=9\]

By taking square roots on both sides of the equation we will get,

\[\therefore d=\pm 3\]

Therefore d = 3 OR d = -3 ……………………………………. (4)

Now we will rewrite the three numbers below,

(a – d), a, (a + d)

If we put the values of equation (2) and equation (4) in above equation as shown below,

a = 4 and d = 3

Therefore numbers will become,

(4 – 3), 4, (4+3)

Therefore the numbers are,

1, 4, 7.

Now,

a = 4 and d = - 3

Therefore numbers will become,

[4 – (-3)], 4, [4+(-3)]

(4 + 3), 4, (4 – 3)

Therefore the numbers are,

7, 4, 1.

Therefore the three numbers are 1, 4, 7 or 7, 4, 1.

Note: Assume the standard numbers given by (a – d), a, (a + d) to make the calculations easier. Also in the step ${{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ you can also use the formulae of \[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]